Correlations among seed traits: implications for breeding high oil yield in safflower (Carthamus tinctorius L.): CORRELATIONS AMONG SEED TRAITS: IMPLICATIONS FOR BREEDING HIGH OIL YIELD IN SAFFLOWER - K SAISANTHOSH; T JOSEPH RAJU; P KADIRVEL; K KESHAVALU; RAZIA SULTANA; PRADUMAN YADAV; N MUKTA (Journal of Oilseeds Research, 2018)
Seed traits are critical determinants of oil yield and quality in safflower. In this study, correlations among a set of seed traits (physical, physiological, biochemical) were studied and compared in a subset of germplasm and a pedigree based population (F3). Some previously published correlations among physical (seed size, weight, hull content, hull type) and biochemical (oil content, fatty acid composition) traits in germplasm could be redetected in F3 population and some disappeared. In germplasm, physiological traits (germination, vigour) did not show correlation with oil content while vigour was positively correlated with seed size and test weight. Contrary to observations in germplasm, seed weight was not correlated with hull content and oil content in F3 population. This is an interesting observation because it raises the possibility ofimproving seedweight and oil content simultaneously and without affecting the hull proportion, which is critical for breeding high oil yield in safflower.